Efek Freezing Damages dan Temperatur Distilasi terhadap Hasil Minyak Atsiri (Nilam) - Hamidi, Nurhkolis; Ariyanto, Adhy; Sasongko, Mega Nur; Sugiarto, Sugiarto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Essential oils are a great group of vegetable oils in the form a viscous liquid at room temperature but easily evaporate so as to provide a distinctive scent. Indonesia is the world's largest patchouli oil each year to supply about 75% of the world, but seen from the quality and quantity did not experience much change. This is due to most of the units of the oil still using simple technology / traditional and generally has a limited production capacity. Problems like this need to find a solution with one of the ways that pre-distillation using a freezing effect on the leaf so that the cells will be damaged so that the distillation process will be easier and get the quality of good patchouli oil. Freezing performed on fresh leaves and stems with a temperature variation of 13.8, -19.6 and -24.8 Âº C, while the temperature of distillation varies the 95, 105 and 115 Âº C, the clotting time for 2 hours. The results showed the presence of the lower freezing temperature the higher freezing the higher the content of patchouli alcohol (C15H26O), was to the effect of the higher distillation temperature distillation temperatures accelerate the process of spending patchouli oil from the leaves and stems.Keywords: Essential Oil, Predistillation, Temperature, Patchouli Alcohol (C15H26O)